Characteristics of individuals with tuberculosis in an urban, poor population in Osaka City, Japan — a case-control study (Western Pacific Surveillance and Response, 2020)
Objective: To identify individual characteristics related to the development of pulmonary tuberculosis (PTB) among residents in the Airin area (Airin), Osaka City, Japan.Methods: We conducted a retrospective case-control study of individual characteristics potentially related to the development of PTB by comparing PTB patients and residents without tuberculosis (TB) in Airin. The following binominal data of characteristics were compared: age ( 65); body mass index (BMI) ( 18.5); diabetes mellitus (diagnosed or not diagnosed); smoking (currently smoking any amount or not smoking); and alcohol use (currently drinking any amount or not drinking).Results: We compared the individual characteristics of 192 PTB patients notified from January 2015 to December 2018 and 190 residents of supportive houses who attended a health education programme from April 2016 to March 2018.Univariable analysis showed that the following characteristics were significantly related with PTB: BMI